2005
DOI: 10.1111/j.1610-0387.2005.04799.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapie des Erysipels in Deutschland und Österreich – Ergebnisse einer Umfrage an deutschen und österreichischen Hautkliniken

Abstract: The majority of clinics treat patients with erysipelas as inpatients with intravenous antibiotics. The usual first line treatment is group G penicillin (80%). Other choices include amino-penicillins (11%), cephalosporins (16.5%) and anti-staphylococcal penicillins (6.9%) are used. As second line antibiotics macrolides (63.5%), clindamycin (52.5%), penicillins (18.5%), cephalosporins (40%) and fluoroquinolones (20.5%) are mentioned. Carbapenems, tetracyclines, nitroimidazoles, glycopeptides, aminoglycosides, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There is no data available that demonstrates, how many patients with cellulitis of the upper extremity receive prophylactic anticoagulation. A study performed by Brennecke et al [25]. showed that prophylactic anticoagulation is applied only to 38 to 45 % of all patients with cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…There is no data available that demonstrates, how many patients with cellulitis of the upper extremity receive prophylactic anticoagulation. A study performed by Brennecke et al [25]. showed that prophylactic anticoagulation is applied only to 38 to 45 % of all patients with cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…None of the centers was a referral center for erysipelas, thus being representative of the population they service. Patients described in our study were seen during the clinical routine, and erysipelas was diagnosed by a dermatologist based on established clinical and laboratory criteria [3,8,9]. All relevant demographic, clinical and therapy-related parameters and laboratory signs of inflammation of patients with erysipelas on the thighs or buttocks were entered in a database.…”
Section: Methodsmentioning
confidence: 99%
“…Direct detection of the etiological agent and serology are not helpful in clinical routine [3,6,7]. Treatment with β-lactam antibiotics is sufficient in most cases [8]. The development and course of erysipelas is associated with systemic and/or local risk factors.…”
Section: Introductionmentioning
confidence: 99%